Oncolytic adenovirus encoding variant interleukin-2 combined with chemotherapy enables PD-L1 inhibition in pancreatic cancer models - Santeri A. Pakola; Nea Ojala; Tatiana V. Kudling; James H. A. Clubb; Elise Jirovec; Mirte van der Heijden; Victor Arias; Lyna Haybout; Saru Basnet; Susanna Grönberg-Vähä-Koskela; Dafne C. A. Quixabeira; Joao M. Santos; et al. (Cancer Immunology, Immunotherapy)
Abstract Pancreatic ductal adenocarcinoma (PDAC) is a cancer with dismal prognosis due to resistance to most current therapies. Although immunotherapy has improved the treatment of many solid cancers, pancreatic cancer remains resistant to immunotherapy due to immunosuppressive tumor microenvironment, limited lymphocyte infiltration and lack of neoantigens. Oncolytic adenoviruses are a possible solution to treatment resistance in PDAC due to their ability to elicit lymphocyte trafficking and epitope spreading. Herein, we tested if an oncolytic adenovirus encoding a variant interleukin-2 molecule (Ad5/3-E2F-d24-vIL2), could enable immune checkpoint inhibitor (ICI) therapy in PDAC when combined with chemotherapy. Rationale for Ad5/3-E2F-d24-vIL2 was tested in vitro, where increase in programmed death ligand 1 (PD-L1) expression was seen after virotherapy and chemotherapy. Expression of other B7 family proteins was characterized in mono- and co-culture settings of cancer cells, fibroblasts, and macrophages. The combination therapy of virotherapy, chemotherapy and ICI was characterized in freshly resected ex vivo pancreatic tumor samples. Combination of ICI with virotherapy showed increased interferon and chemokine production in samples, with expansion of cytotoxic CD8 + T cells seen by flow cytometry. In vivo evaluation of the triple combination therapy in a Syrian hamster model showed improved tumor growth control and overall survival, with concurrent increase in intratumoral lymphocytes during therapy. Animals cured with the therapy showed resistance to re-challenge with the same cell line, supportive of successful generation of anti-tumor immunity in the animals. The combination treatment of Ad5/3-E2F-d24-vIL2, chemotherapy, and checkpoint inhibition is a promising treatment modality to tackle treatment resistance in PDAC.